The Implementation and Evaluation of the South African Adaptation of the JOBS Program - Paver, Rachele; De Witte, Hans; Rothmann, Sebastiaan; Van den Broeck, Anja; Blonk, Roland Willem Bart (Frontiers in Psychology, 2020)
No validated intervention that specifically addresses the psychosocial needs of unemployed people exists in the South African context. This study intends to evaluate an evidence-based job-search program, called the JOBS intervention, that is aimed at the self-efficacy, amotivation, and self-esteem related to participants searching for jobs. A quasi-experimental research design was used. Convenient samples were taken of unemployed individuals from two low-income communities (N = 130; experimental group = 69; control group = 61). The Qhubekela Phambili program, which is based on the JOBS program, was adapted for the South African context and was implemented over six four-hour sessions. Data collection took place pre- and post-intervention. One-way analysis of covariance was used to analyze the data. Those who had undergone the intervention showed statistically significantly higher levels of job-search self-efficacy and self-esteem. This study makes a novel contribution to the literature on the JOBS program, particularly regarding developing countries. This study showed that in a context characterized by poverty and a lack of support for the unemployed, the program also delivered promising results. It confirms previous findings that the JOBS program is suitable in a variety of labor market and economic conditions.